Congenital stenosis of the anal canal. Clinical case - Carro, Gabriela; Salsamendi, José; Puglia, Paul; Giannini, Gabriel (Cirugía del Uruguay, 2024)
Anal canal stenosis is a rare form of anorectal malformation, representing 1%. There are few registered cases and there is little literature on this entity. It is an entity where the anus presents a stenosis of variable length, is normo-implanted, with a normal appearance, surrounded by an adequate sphincter complex. The presence of associated cardiovascular, renal, and osteoarticular malformations must be ruled out, and especially the presence of a presacral mass must be evaluated, which may present teratomas, anterior myelomeingocele, among others. Surgical treatment consists of respecting the sphincter complex through a posterior approach, without dissection of the anterior face of the rectum. Due to the presence of a normal surrounding sphincter complex, the intestinal functional prognosis of these patients is excellent. We present the first clinical case in our setting of a patient with stenosis of the anal canal, its form of presentation, surgical treatment and evolution.